Offenses of service - Negligence at work. Critical Opinions: Array - Bîrzu, Bogdan (Acta Universitatis Danubius. Juridica, 2020)
In the content of the article we proceeded in examining the constitutive content of the crime of negligence in the service, with emphasis on the objective and subjective side. On the occasion of the analysis, we referred to the recent judicial practice in the matter, as well as to the considerations of two decisions of the Constitutional Court regarding this crime. From the perspective of repealing the legal norm of criminal law, we insisted on formulating a critical opinion regarding this action of the legislator, arguing the need to maintain the incrimination. The study is part of a course to be published in the next period at a recognized publishing house in the field. This paper can be useful both to students and masters of the profile faculties in the country, as well as to practitioners in the field of criminal law.